Climate Change and Rural Development: A Bibliometric Review - Yudiatmaja Wayu Eko; Setiawan Ramadhani; Poti Jamhur; Alfiandri Alfiandri; Hendrayady Agus; Azizi Okky Rizki; Caraka Rezzy Eko (BIO Web of Conferences)
This study addresses the gaps in the current literature by reviewing the intellectual structure and research trends on climate change and rural development. This research aims to identify contributed authors, journals, countries, articles, and key topics in these research areas. We used a bibliometric approach to analyse the performance of the literature and knowledge structure of the issues from 492 articles from 1996 to 2023 indexed by the Web of Science. Our findings reveal that Land Use Policy is the leading journal of publications and citations, reflecting its prominent role in disseminating research on climate change and rural development. Silva emerges as an influential author, contributing significantly to the discourse. Geographically, the United States leads in research output, highlighting its strong focus on addressing rural development challenges in the context of climate change. Using co-occurrence analysis, we reveal several terms in climate change and rural development research, including energy, vulnerability, biodiversity, and biomass. This study systematically reviews these issues and contributes to climate change and rural development.